A Strong Family System From The Perspective Of Minangkabau Women; Qualitative Interviews With Ethnic Minang Wives And Bundo Kanduang - Tesi Hermaleni; Diana Setiyawati; John Defrain (Green Publisher, 2025)
This research aims to get an overview of a strong family system from the perspective of Minangkabau women. A qualitative interview method id used to achieve the research objective. Two types of participants were involved in this research: Bundo Kanduang and ethnic Minangkabau wives. The number of participants in this study were 4 Minangkabau ethnic wives and 1 Bundo Kanduang. As for getting participants, the researcher used snowballing sampling. Data were obtained through in-depth interviews via mobile phone and Zoom and then analyzed using inductive thematic analysis using data analysis software MAXQDA. The study’s result revealed differences in the ideal and factual family systems of ethnic Minangkabau women. However, two ideal aspects still exist in Minangkabau ethnic families, namely the application of Islamic values and the Qur’an in Minang family life, as well as the division of men's roles as breadwinners and the dominance of women in the household. The extended family in the results of this study is the samande family, which has a crucial role as a strong batih family support system. In other words, it can be said that the Minangkabau family does not necessarily only become a nuclear family today.